2020
DOI: 10.1088/1748-9326/ab6561
|View full text |Cite
|
Sign up to set email alerts
|

Regime shift of the hydroclimate–vegetation system in the Yellow River Delta of China from 1982 through 2015

Abstract: The Yellow River Delta (YRD) has been experiencing substantial climatic, hydrological, and anthropogenic stresses, and a sound understanding of the regime shift in its hydroclimate-vegetation system is of fundamental importance for maintaining the health and stability of its regional ecosystems. This study constructs and analyzes a 34-year-dataset (1982-2015) of hydro-climatic variables and satellite-based Normalized Difference Vegetation Index (NDVI) in the YRD. A seasonaltrend decomposition technique based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…(c) indicates the newly added areas of each land use type. Furthermore, climate change played a significant role in the vegetation variations observed in the YRD.Previous research has indicated that temperature is a key driving factor for spring and autumn vegetation growth, while precipitation is an important hydrological factor affecting vegetation growth, besides the impact of runoff[7]. This study demonstrates the enormous potential of multisource remote sensing data fusion methods for the monitoring of vegetation changes in estuarine wetlands.…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…(c) indicates the newly added areas of each land use type. Furthermore, climate change played a significant role in the vegetation variations observed in the YRD.Previous research has indicated that temperature is a key driving factor for spring and autumn vegetation growth, while precipitation is an important hydrological factor affecting vegetation growth, besides the impact of runoff[7]. This study demonstrates the enormous potential of multisource remote sensing data fusion methods for the monitoring of vegetation changes in estuarine wetlands.…”
mentioning
confidence: 65%
“…Vegetation is the fundamental basis of ecosystem services and functions, and its dynamics act as a sensitive indicator of ecosystem conditions, being closely related to climate change, hydrological conditions, and human activities [7]. In recent years, the rapid development of remote sensing technology has led to it becoming the primary approach used to study wetland evolution processes and patterns.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations